Preparation of Atomic Entangled States and Schrödinger Cat States for N Trapped Ions Driven by Frequency-Modulated Laser (Journal of Atomic and Molecular Sciences, 2014)
We propose a news cheme to prepare the Greenberger-Horne-Zeilinger statesand atomic Schrödinger cat states for N trapped ions. This scheme is based on the interactionof N trapped ions with a frequency-modulated traveling wave light field.Preparations of these states can be all complished by one-step operation.
Keywords: trapped ion; entanglement state; atomic Schrödinger cat; frequency modulation.